The Effect Of Tax Sanctions, Tax Knowledge, And Tax Socialization On Individual Taxpayer Compliance With Taxpayer Awareness As A Mediation Variable - Frecky; H. Waluyo (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the effect of tax sanctions, tax knowledge, and tax socialization on individual taxpayer compliance, with taxpayer awareness as a mediating variable. Using a quantitative approach with the Structural Equation Modeling-Partial Least Square (SEM-PLS) method, data were collected via questionnaires from 100 individual taxpayers in Jakarta. The results indicate that: (1) tax sanctions have a significant positive effect on taxpayer compliance; (2) tax knowledge significantly improves compliance; (3) tax socialization positively impacts compliance; (4) taxpayer awareness significantly enhances compliance; and (5) taxpayer awareness successfully mediates the effects of tax sanctions, tax knowledge, and tax socialization on compliance. These findings underscore the importance of fiscal policies that prioritize compliance through taxpayer awareness, particularly among Micro, Small, and Medium Enterprises (MSMEs).